Short Communication: Assessment of cogongrass (Imperata cylindrica (L.) P.Beauv.) genetic variation in Java, Indonesia using atpB-rbcL and trnL-F intergenic spacer (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Susanto AH, Dwiati M. 2022. Short Communication: Assessment of cogongrass (Imperata cylindrica (L.) P.Beauv.) genetic variation in Java, Indonesia using atpB-rbcLand trnL-F intergenic spacer. Biodiversitas 23: 2760-2767. Cogongrass (Imperata cylindrica(L.) P.Beauv.) is an invasive species commonly found in tropical and subtropical regions worldwide, consequently threatening global plant biodiversity, and sustainable agriculture. Nevertheless, some of its potential as a medicinal herb, phytoremediation agent, and alternative energy have been reported. genetic variation of cogongrass has been studied in certain areas, however genetic variation in Java, Indonesia has not been reported. Therefore, this study aims to assess the genetic variation of cogongrass in Java, Indonesia using atpB-rbcLand trnL-F intergenic spacer (IGS). Twenty-one plant samples were collected randomly from nine different sites and two pairs of universal primers were employed to amplify the markers. The results showed a much lower genetic difference among subpopulations in comparison to genetic variation within individual subpopulations. This result indicates that the subpopulations have high connectivity, meaning the rapid change in terrestrial ecosystems on the island does not affect the cogongrass population.